Gastroprotective activity of Banana peel (Musa paradisiaca var. sapientum) methanol extract purified on aspirin-induced gastric ulceration in Rats - Pusmarani, Jastria; Putri, Risky Juliansyah; Dewi, Citra; Fitriani, Difa; Purwono, Setyo; Ikawati, Zullies (Pharmaciana, 2024)
Banana (Musa paradiasiaca var. sapientum) is the world's most popular fruit-bearing crop, with rising consumption and waste. This study aimed to measure the metabolite compound and evaluate the gastroprotective properties of a banana peel-purified methanol extract. Animals test used in this study were divided into six groups: Group One received NaCMC 0.5%, Group Two received sucralfate, Group Three received aspirin 1000 mg/kg body weight, and groups four, five, and six received PBP at doses of 200 mg/kg body weight, 400 mg/kg body weight, and 600 mg/kg body weight, respectively, for seven days. Except for group 1, all groups were induced with aspirin at 1000 mg/kg body weight on the eighth day. The result of this study exhibited banana peel containing total phenolic, flavonoid, and tannin compounds with concentrations of 33.45 mg GAE/g, 19.92 mg QE/g, and 0.16 %, respectively. The results showed that pure extract of Musa paradiasiaca var. sapientum fruit peel can reduce the incidence of gastric ulcers by decreasing the ulcer index (p<0.05).. The results suggested that Musa paradisiaca var. sapientum peel has a gastroprotective effect against aspirin-induced gastric ulceration.